Self-presentation of extraversion shifts all the Big Five personality traits in a socially desirable direction - Sasuke Ueda; Shinji Yamagata (International Journal of Personality Psychology)
The internalization of self-presentation (IOSP; Tice, 1992) is a phenomenon where individuals internalize presented traits (e.g., extraversion) and shift the level of their traits in the presented direction. While IOSP predicts self-concept shifts only in the presented traits, this pre-registered study examined whether self-concepts of non-presented traits also shift in socially desirable directions. Based on statistical power analyses, 89 Japanese undergraduate students were recruited. They completed measures of the Big Five personality traits at two time points: 7–10 days prior to and immediately following a task where they wrote a self-introduction designed to convey an extraverted impression. Paired t-tests revealed shifts in all the Big Five traits in the predicted socially desirable directions (Cohen's |dz| = .29–.36). These findings suggest that self-presentation of extraversion influences the self-concept of both presented and non-presented traits, challenging the current understanding of IOSP. Possible mechanisms underlying this phenomenon and implications for future research on personality change are discussed.